Histopathological Changes In Gill And Hepatopancreas Of Mangrove Crab, Perisesarma Bidens Exposed To Profenofos - A. Maharajan, (Zenodo, 2018)
The purpose of the present study is to provide information on the effect of profenofos on the crab, Perisesarma bidens, a biologically significant mangrove crab. The crabs were exposed to profenofos concentrations of 0.038 ppm and 0.076 ppm (sublethal) for 28 days. The exposed gill tissue exhibited epithelial edema, necrosis, lifting, fusion of secondary lamellae etc. The histopathological symptoms in hepatopancreas were infiltration, large lumen formation and disappearance and bursting of haemocytes. In man, consumption of these crabs will cause the ill effects that are specific to the toxicant. This process will damage the organism silently, without causing any immediate abrupt changes. The changes may be at genetic levels inducing genotoxicity, but concerted effort in reducing the use of profenofos and implementing natural remedies for disease control in shrimp hatchery can help resolve the problem toxicant. : {"references": ["Alazemi, B.M., Lewis, J.W. and Andrews, E.B., 1996. Gill damage in the freshwater fish Gnathonemus ptersii (Family: Mormyridae) exposed to selected pollutants: an ultra structural study. Environ. Technol., 17, 225-238.", "APHA, 1985. Standard methods for the examination of water and waste water APHA, AWWA and WPCF, New York.", "Arellano, J.M., Storch, V. and Sarasquete, C., 2004. Ultrastructural and histochemical study on gills and skin of the Senegal sole, Solea senegalensis. J. Appl. Ichthyol., 20, 452-460.", "Banni, M., Jebali, J., Daubeze, M., Clerandau, C., Guerbej, H. and Narbonne, J.F., 2005. Monitoring pollution in Tunisian coasts: application of a classification scale based on biochemical markers. Biomar., 10, 105-116.", "Baticados, M.C.L. and Tendencia, E.A., 1991. Effects of gusathion A on the survival and shell quality of juvenile Penaeus monodon. Aquacul., 93, 9-19.", "Bela, Z. and Prasad, R., 2008. Impact of pollution on fresh and marine water resources. J.Poll. Res., 273, 461-466.", "Bigi, R., 1996. Efectos del cadmio sobre la fisiolog\u0131\u00b4a branquial de Chasmagnahtus granulata (Decapoda, Brachyura). Graduate Thesis, University of Buenos Aires.", "Bodhipaksha, N. and Weeks-Perkins, B.A., 1994. The effects of methyl parathion on phagocytosis and respiratory burst activity of tiger shrimp (Penaeus monodon) phagocytosis. In: J.S. Stolen, T.C. Fletcher (Eds.), Modulators of Fish Immune Responses, Models for Environmental Toxicology Biomarkers Immunostimulators, vol. 1, SOS Publication, Fair Haven, N.J., pp.11-12.", "Caceci, T., Neck, K.F., Lewis, D.H. and Sis, R.F. 1988. Ultrastructure of the hepatopancreas of the pacific white shrimp, Penaeus vannamei (Crustacea: Decapoda). J. Mar. Biol. Assoc. UK., 68, 323-337.", "Dall, W. and Moriarty, D.J.W., 1983. Functional aspects of nutrition and digestion. In:Mantel, L.H. (Ed.), The Biology of Crustacea. Internal Anatomy and Physiological Regulation, vol. 5. Academic Press, New York, pp. 215-261.", "Evans, D.H., Piermarini, P.M. and Choe, K.P., 2005. The multifunctional fish gill: dominant site of gas exchange, osmoregulation, acid-base regulation, and excretion of nitrogenous waste. Physiol. Rev., 85, 97-177", "Gavrilescu, M., 2005. Fate of pesticides in the environment and it's bioremediation. Eng. Life Sci., 5(6), 497- 526.", "Ghazala, M., Mahboob, S., Al-Ghanim, K.A., Sultana, S., Alkahem Al-Balawi, Sultana, T., Al-Misned, F. and Ahmed, Z., 2014. Acute toxicity II: Effect of organophosphates and carbamates to Catla catla. J. Anim. Plant Sci., 24, 1795-1801.", "Hart, K. and Pimentel, D., 2002. Public health and costs of pesticides. In: Encyclopedia of pest management (ed. D. Pimentel). Marcel Dekker, New York, pp. 677-679.", "Johnston, D.J., Alexander, C.G. and Yellowhees, D., 1998. Epithelial cytology and function in the digestive gland of Thenus orientalis (Decapoda, Scyllaridae). J. Crust. Biol., 18, 271-278.", "Krishnamoorthy, P. and Subramanian, P., l996. Effect of sub lethal doses of copper on the hepatopancreas of the freshwater prawn, Macrobrachium lamarrei lamarrei Geobio., 23(1), 16-18.", "Lundbaye, A.K., Curtis, T.M., Braven, J. and Depledge, M.H., 1997. Effects of the organophosphorous pesticide, dimethoate, on cardiac and acetylcholinesterase (AChE) activity in the shore crab Carcinus maenas. Aquat. Toxicol., 40, 23-36.", "Maharajan, A., Narayanasamy, Y., Ganapiriya, V. and Shanmugavel, K., 2015. Histological alterations of a combination of Chlorpyrifos and Cypermethrin (Nurocombi) insecticide in the fresh water crab, Paratelphusa jacquemontii (Rathbun). J. Basic Appl. Zool., 72, 104-112.", "Maharajan, A., Neelakandamoorthy, N. and Kumarasamy, P. 2012a. Impact of Profenofos on oxygen consumption and gill histopathology of the Fresh water crab, Paratelphusa jacquemontii (Rathbun). Res. Rev. J. Toxicol., 2(2), 46-55.", "Maharajan, A., Rajalakshmi, S., Vijayakumaran, M. and Kumarasamy, P. 2012b. Sublethal effect of copper toxicity against histopathological changes in the spiny lobster, Panulirus homarus (Linnaeus, 1758). Biol. Trace Elem. Res., 145, 201-210.", "Maharajan, A., Usha, R., Paruruckmani, P.S., Vijaykumar, B.S., Ganapiriya, V. and Kumarasamy, P. 2013. Sublethal effect of profenofos on oxygen consumption and gill histopathology of the Indian major carp, Catla catla (hamilton) Int. J. Pure Appl. Zool., 1(1), 196-204.", "Mahboob, S., Ghazala, Sultana, S., Al-Akel, A.S., Humood, F.A.B., Al-Misned, F. and Zubair, M., 2011. Pesticide residues in flesh of Cirrhinus mrigala collected from a commercial farm and river Chenab at Trimu Head, Jhang. Paki. J. Zool., 43, 97-101.", "Oliveira Ribeiro, C.A., Vollaire, Y., Sanchez-Chardi, A. and Roche, H., 2005. Bioaccumulation and the effects of organochlorine pesticides, PAH and heavy metals in the eel (Anguilla anguilla) at the Camargue Nature Reserve, France. Aquat. Toxicol., 74, 53-69.", "Randi, A.S., Monserrat, J.M., Rodr\u0131\u00b4guez, E.M. and Romano, L.A., 1996. Histopathological effects of cadmium on the gills of the freshwater fish, Macropsobrycon uruguayanae Eigenmann (Pisces, Atherinidae). J. Fish. Dis., 19, 311-322.", "Victor, B., Mahalingam, S. and Sarojini, R., l985. Cytopathological effects of cadmium on the freshwater prawn Macrobrachium idea. Ind. J. Fish., 32(4), 478-80.", "Vigliano, F.A., Aleman, N., Quiroga, M.I. and Nieto, J.M., 2006. Ultrastructural Characterization of Gills in Juveniles of the Argentinian Silverside, Odontesthes bonariensis (Valenciennes, 1835) (Teleostei: Atheriniformes). Anat. Histol. Embryol., 35, 76-83.", "Viswanathan, S. and Manisseri, M.K., l995. Histopathological studies on Zinc toxicity in Penaeus indicus H. Milne Edwards. Mariculture Research under the postgraduate programme in Mariculture Part-6. Rengarajan, K. (eds.), Cochin India, CMFRI No. 61, 25-29.", "Wanee, J., Upatham, E., Maleeya, K., Somphong, S., Grams, S. and Prayad, P., 2002. Histopathological effects of Roundup, a Glyphosate herbicide on Nile tilapia (Oreochromis niloticus), Sci. Asia, 28, 121- 127.", "Zeeman, M.G. and Brindley, W.A. 1981. Effects of toxic agents upon fish immune systems: a review. In: Immunologic Considerations in Toxicology. (R. P. Sharma, ed.). Boca Raton, FL: CRC Press/Lewis Publisher. pp. 1-60."]}